Lymphoid Infiltrates in B Cell Non Hodgkin’s Lymphoma: Comparing Nuclear Characteristics between Lymph Node and Bone Marrow; and Evaluating Diagnostic Features of Bone Marrow Infiltrates in Paraffin Embedded Tissues - Mark H. Deverell; Elizabeth Best; Jonathan R. Salisbury (Analytical Cellular Pathology)
Distinguishing non Hodgkin’s lymphoma from benign lymphoid aggregates in bone marrow is well recognised to be difficult. Our objective was to evaluate nuclear morphology, and to perform morphometry on benign and neoplastic lymphoid infiltrates, to establish if objective criteria were of value in the diagnosis of neoplasia. By comparing neoplastic infiltrates in bone marrow with infiltrates in lymph nodes, the validity of grading non Hodgkin’s lymphoma on the basis of bone marrow histology alone was assessed. 82 cases of B cell non Hodgkin’s lymphoma (44 low grade and 38 high grade), known to have both lymph node and bone marrow involvement at the time of presentation, were compared with bone marrow trephines containing reactive lymphoid infiltrates.